Alcohol Abstinence Rescues Hepatic Steatosis and Liver Injury via Improving Metabolic Reprogramming in Chronic Alcohol-Fed Mice - Pi, Aiwen; Jiang, Kai; Ding, Qinchao; Lai, Shanglei; Yang, Wenwen; Zhu, Jinyan; Guo, Rui; Fan, Yibin; Chi, Linfeng; Li, Songtao (Frontiers in Pharmacology, 2021)
Background: Alcoholic liver disease (ALD) caused by chronic ethanol overconsumption is the most common type of liver disease with a severe mortality burden throughout the world. The pathogenesis of ALD is complex, and no effective clinical treatment for the disease has advanced so far. Prolonged alcohol abstinence is the most effective therapy to attenuate the clinical course of ALD and even reverse liver damage. However, the molecular mechanisms involved in alcohol abstinence-improved recovery from alcoholic fatty liver remain unclear. This study aims to systematically evaluate the beneficial effect of alcohol abstinence on pathological changes in ALD. Methods: Using the Lieber-DeCarli mouse model of ALD, we analysed whether one-week alcohol withdrawal reversed alcohol-induced detrimental alterations, including oxidative stress, liver injury, lipids metabolism, and hepatic inflammation, by detecting biomarkers and potential targets. Results: Alcohol withdrawal ameliorated alcohol-induced hepatic steatosis by improving liver lipid metabolism reprogramming via upregulating phosphorylated 5’-AMP -activated protein kinase (p-AMPK), peroxisome proliferator-activated receptor-α (PPAR-α), and carnitine palmitoyltransferase-1 (CPT-1), and downregulating fatty acid synthase (FAS) and diacylglycerol acyltransferase-2 (DGAT-2). The activities of antioxidant enzymes, including superoxide dismutase (SOD) and glutathione peroxidase (GSH-px), were significantly enhanced by alcohol withdrawal. Importantly, the abstinence recovered alcohol-fed induced liver injury, as evidenced by the improvements in haematoxylin and eosin (H&E) staining, plasma alanine aminotransferase (ALT) levels, and liver weight/body weight ratio. Alcohol-stimulated toll-like receptor 4/mitogen-activated protein kinases (TLR4/MAPKs) were significantly reversed by alcohol withdrawal, which might mechanistically contribute to the amelioration of liver injury. Accordingly, the hepatic inflammatory factor represented by tumour necrosis factor-alpha (TNF-α) was improved by alcohol abstinence. Conclusions: In summary, we reported that alcohol withdrawal effectively restored hepatic lipid metabolism and reversed liver injury and inflammation by improving metabolism reprogramming. These findings enhanced our understanding of the biological mechanisms involved in the beneficial role of alcohol abstinence as an effective treatment for ALD.